Grid-tied 15-level Cascade Inverter with Predictive Current Control - Pastor, M.; Dudrik, J. (Elektronika ir Elektrotechnika, 2012)
The paper presents a grid-tied cascade H-bridge inverter with predictive current control. The proposed 15-level cascade inverter consists of three H-bridge inverters with separated DC sources. At the output of the cascade inverter an L filter is used. The cascade inverter is controlled by the mean of RT-Lab. The predictive current regulator and one-phase synchronous reference frame PLL are designed with help of Rapid Control Prototyping. The proposed control method uses a discrete model of the load to predict the behaviour of the system for each of 15 voltage levels of inverter’s output voltage. Verification on a laboratory model is described. DOI: http://dx.doi.org/10.5755/j01.eee.18.9.2798